The Child Tax Credit over Time by Family Type: Benefit Eligibility and Poverty - Margaret E. Brehm; Olga Malkova (Institute of Labor Economics (IZA), 2023)
We examine disparities in Child Tax Credit (CTC) eligibility and anti-poverty effects since 1998 by family type. Initially, single mothers were least likely to be eligible and were underrepresented among those lifted from poverty by the CTC, because the credit was virtually nonrefundable. By 2017, disparities by family type mostly disappear, as eligibility and anti-poverty effectiveness of the CTC among single mothers increases dramatically, because of reforms increasing CTC refundability. When the credit doubles in 2018, disparities revert toward initial levels, as eligibility and the anti-poverty effectiveness of single mothers rises least, because of a phaseout threshold expansion and partial refundability.
Keywords: H24; H71; J22; 330; Child Tax Credit; poverty; gender; tax policy